[tex]~~~~~~~~~~~~\textit{quadratic formula} \\\\ \stackrel{\stackrel{a}{\downarrow }}{3}x^2\stackrel{\stackrel{b}{\downarrow }}{+2}x\stackrel{\stackrel{c}{\downarrow }}{+4}=0 \qquad \qquad x= \cfrac{ - b \pm \sqrt { b^2 -4 a c}}{2 a} \\\\\\ x= \cfrac{ - (2) \pm \sqrt { (2)^2 -4(3)(4)}}{2(3)}\implies x=\cfrac{-2\pm \sqrt{4-48}}{6}[/tex]
[tex]x=\cfrac{-2\pm \sqrt{-44}}{6}\implies x=\cfrac{-2\pm \sqrt{(-1)(2^2)(11)}}{6}\implies x=\cfrac{-2\pm 2~i\sqrt{11}}{6} \\\\\\ x=\cfrac{2(-1\pm i\sqrt{11})}{6}\implies x=\cfrac{-1\pm i \sqrt{11}}{3}[/tex]
mind you that it has two complex roots, or imaginary values.